Digital storytelling across the life course: Protocol for a theory-based analysis - Steven Hall; Michael Lang; Lauren Czarniewski; Cavan Fani; Ziyu Li; Kathleen Shearer (PLoS ONE, 2026)
Background Digital storytelling (DST) combines first-person narratives with images, sound, and video to convey health experiences, empower under-represented voices, and foster empathy. Insight into how digital stories portray life-course influences remains scarce. Guided by the Life Course Health Development (LCHD) framework, this study protocol describes a planned theory-based analysis of 105 publicly available digital story videos from Alberta Health Services (AHS). We aim to (1) map representations of cumulative exposures, critical periods, and transitions across stories spanning childhood to late adulthood; and (2) generate guidance for using DST to strengthen partnerships among patients, caregivers, clinicians, and policymakers. Methods We present our detailed methods for our planned study within this protocol using the Standards for Reporting for Qualitative Research checklist. Our team will review each video in AHS’ DST repository with a structured data collection form, capturing storyteller demographics, life-course stage, clinical context, LCHD constructs, and reflexive notes. Directed content analysis of our data collection forms will be performed in NVivo 14 with a hybrid coding approach: deductive codes to mirror core LCHD concepts and inductive codes to capture context-specific themes. Discussion Insights from this study will guide clinicians’ life course dialogue, inform health systems’ investment in DST platforms for learning, and assist policymakers in embedding lived experience within equity agendas. The study will yield theoretically grounded recommendations for curating, analyzing, and mobilizing DST libraries across diverse health settings. Protocol Registration: https://doi.org/10.17605/OSF.IO/C5R9T